Inclusion, of Agrobiodiversity management and conservation in the management plans of the Man and the Biosphere Reserves of Cuba, for the first time - CGIAR Research Program on Water, Land and Ecosystems (2019)
The latest management plans of two of the MaB reserves of Cuba have been updated to include the importance of conservation and sustainable use of agrobiodiversity. These plans have been updated in consultation with the farming communities that are the custodians of the rich agrobiodiversity found in these reserves.